Keratosis pilaris and prevalence of acne vulgaris: a cross-sectional study - Schmitt, Juliano Vilaverde [UNESP]; Lima, Brunno Zeni de; Meira do Rosrio de Souza, Monique Carolina; Miot, Hélio Amante [UNESP] (Soc Brasileira Dermatologia, 2014)
BACKGROUND: Acne vulgaris has an important genetic predisposition, as well as keratosis pilaris. Clinical observations suggest that patients with keratosis pilaris have less frequent or less severe acne breakouts; however, we found no studies on this regard OBJECTIVE: To determine if the presence of keratosis pilaris is associated with lower prevalence and severity of acne. METHODS: A cross-sectional study was conducted with dermatology outpatients aged between 14 and 35 years. We evaluated history and clinical grade of acne, demographic variables, history of atopy, smoking, and use of hormonal contraceptives. Two groups were defined by the presence or absence of moderate to severe keratosis pilaris on the arms and were compared by bivariate analysis and by conditional multiple logistic regression. RESULTS: We included 158 patients (66% women), with a median age of 23 +/- 11 years. Twenty-six percent of them had keratosis pilaris, which was associated with a history of atopy (odds ratio [OR]=2.80 [1.36 to 5.75]; p<0.01). Acne was present in 66% of subjects, and was related to family history of acne (OR=5.75 [2.47 to 13.37]; p<0.01). In bivariate and multivariate analysis, the group with keratosis pilaris had a less frequent history of acne (OR=0.32 [0.14 to 0.70]; p<0.01). CONCLUSION: The presence of moderate to severe keratosis pilaris on the arms was associated with lower prevalence of acne vulgaris and lower severity of facial lesions in adolescents and young adults.
Keywords: Acne vulgaris; Chromosomes, Keratosis; pair 18; Risk Factors; human